KEBERADAAN PIDANA MATI DALAM KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) - Kumala Dewi, Ni Komang Ratih (Jurnal Komunikasi Hukum, 2020)
Capital punishment is the heaviest crime and difficult to apply in a country of law considering the death penalty is one of the acts of human rights violations, but to make someone discourage of committing a crime there needs to be rules or penalties that can provide a deterrent effect and provide security for the community from all form of crime. The purpose of writing is directed to find out the regulation of the Death Penalty in the Criminal Law Code which is stipulated in several articles in the Criminal Code and the existence of capital punishment in the legal system in Indonesia in terms of human rights perspective, which of course would be contrary to human rights, especially the right to life, however capital punishment is also needed as an effort to prevent the occurrence of crimes, especially those classified as serious